2013
DOI: 10.1177/0010414013495358
|View full text |Cite
|
Sign up to set email alerts
|

Oil, Democracy, and Context

Abstract: A considerable debate precludes drawing conclusions about oil’s effect on democracy. This article challenges this stalemate by significantly expanding the scope of the previous research and using meta-regression analysis to examine the integrated results of extant scholarship. While the results suggest a nontrivial negative association between oil and democracy across the globe, they also indicate a notable variation in this relationship across world regions and institutional contexts. A conditioning effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 59 publications
0
59
0
2
Order By: Relevance
“…The larger the sample, the greater the statistical power to detect a given genuine effect. 5 Since Cohen (1965), adequate power in most social sciences has been conventionally defined as 80%. That is, the probability of a Type II error should be no larger than four times the probability of the conventional Type I error (0.05).…”
Section: Power and Biasmentioning
confidence: 99%
“…The larger the sample, the greater the statistical power to detect a given genuine effect. 5 Since Cohen (1965), adequate power in most social sciences has been conventionally defined as 80%. That is, the probability of a Type II error should be no larger than four times the probability of the conventional Type I error (0.05).…”
Section: Power and Biasmentioning
confidence: 99%
“…An extreme bounds analysis identified oil dependence as one of the few robust correlates of regime types (Gassebner et al 2012). A statistical meta-analysis of the oil-democracy question, which integrated the results of 29 studies and 246 empirical estimates, concluded that oil had a negative, nontrivial, and robust effect on democracy (Ahmadov 2014). Prichard et al (2014) revisit this issue, using a new and much-improved cross-national dataset on resource revenues and a wide range of econometric tests; they report that government revenues from natural resources have a large, statistically robust effect on autocratic persistence.…”
Section: Resource Wealth and Democracymentioning
confidence: 99%
“…However, more recent researches start to analyze the conditioning effects of political institutions on the existence or extent of the resource curse (Ahmadov, 2014;Aslaksen, 2008, 2013;Bhattacharyya and Hodler, 2010;Luong and Weinthal, 2010). Some studies find that the quality of political institutions strongly moderates the impacts of resources on the economy.…”
Section: Resultsmentioning
confidence: 99%